ECONOMIC EFFECTS OF SUSTAINABLE TOURISM FOCUSED ON GREEN ECONOMY - KONAK, Ali (University Research Base, 2025)
One of the sectors that has become important in terms of national economies in recent years has been the tourism sector. Tourism activities are an extremely important sector in terms of both their diversity and their significant economic contributions to the national economy. In order to develop the tourism sector, which is extremely important in economic terms, it has been observed that significant investments have been made in the tourism sector in recent years. However, it is extremely important that these investments are made without harming the natural environment. For this reason, while carrying out tourism activities and making investments in this sector, it is of great importance to pay attention to the sustainability element and to take into account the needs of the next generations as well as meeting social needs while carrying out tourism activities. This prepared study focuses on the economic importance of green economy-oriented and sustainable tourism activities.